Homeopathic treatment for bone regeneration: experimental study - Almeida, Janete Dias [UNESP]; Loschiavo Arisawa, Emilia Angela; Balducci, Ivan [UNESP]; da Rocha, Rosilene Fernandes; Carvalho, Yasmin Rodarte (Elsevier B.V., 2009)
Aim and method: The objective of this research was to study the effect of homeopathic treatment with Plumbum metallicum (Plumbum met.) on mandibular bone repair in rats.Materials and methods: We analyzed the mandibles of 60 male rats, approximately 3-month-old, randomly divided into three groups of 20 animals each: control, treated with calcitonin, and treated with a homeopathic medicine. A circumscribed bone defect measuring 4 mm in diameter was made in the mandible and covered with a pollytetrafluorethylene (PTFE) barrier. The group treated with calcitonin received 2 IU/kg intramuscularly three times a week; the group treated with Plumbum met. 30c received three drops in water every day. The animals were sacrificed after 7,14,21 and 28 days. The mandibles were removed and submitted to histologic and histomorphometric analyses.Results: Data were analyzed statistically by two-way ANOVA and by the Tukey test. The interaction effect (ANOVA, F df(6; 48) = 4.64; p = 0.001 < 0.05) indicated that the relationship between treatments was not the same at each time of sacrifice. Although statistical analysis of the histomorphometric data showed a similar results for the treated and control groups. But histological analysis showed complete filling of the surgical defect throughout its extent was only for the group treated with Plumbum met.Conclusion: The study demonstrated that for repair of surgical defects in rat mandibles Plumbum met. 30c and control did not differ significantly in histomorphometric terms. Homeopathy (2009) 98, 92-96.
Keywords: Calcitonin; bone regeneration; homeopathy; Plumbum metallicum